Shipping - into the future : regulatory, technology, and operation - Wong, Qing Le (2019)
Automation is the use of integrated technology to develop intelligent solutions to improve operational efficiency and safety. Ship automation and drones automation enhances shipboard operations to be more efficiently performed. While on the other hand, port automation enables the control of vessel traffic and trade flow efficiently thereby increasing port’s productivity and efficiency.